Systematic review of adjuvant therapy for early stage (epithelial) ovarian cancer. Issue 4 (1st June 2003) - Winter-Roach, B.; Hooper, L.; Kitchener, H.
Abstract : A systematic review and meta analysis has been undertaken in order to evaluate the effectiveness of adjuvant therapy following surgery for early ovarian cancer. Trials reported since 1990 have been of a higher quality enabling a meta analysis of adjuvant chemotherapy vs adjuvant radiotherapy and a meta analysis of adjuvant chemotherapy vs observation. There was no significant difference between radiotherapy and chemotherapy, though these comprised studies which demonstrated considerable heterogeneity. Chemotherapy did confer significant benefit over observation in terms of both overall and disease free survival. Except for women in whom adequate surgical staging has revealed well differentiated disease confined to one or both ovaries with intact capsule, platinum chemotherapy should be offered to reduce risk of recurrence.